Prevalence and Associated Factors of Pesticide Poisoning among Farmers in Rural Indonesia: A Cross-Sectional Study - Helfi Nolia; Risnawati Tanjung; Defi Ermayendri; Deri Kermelita (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2026)
Background: Pesticide poisoning is a significant occupational health problem among farmers in developing countries. In Indonesia, 710 cases of pesticide poisoning were reported in 2014. In Pematang Raya Village, Simalungun Regency, blood cholinesterase examinations have never been conducted due to high costs, resulting in the absence of prevalence data on pesticide poisoning.Methods: This study used a cross-sectional design conducted in Pematang Raya Village, Simalungun Regency, with a total sample of 43 farmers selected using purposive sampling. Blood cholinesterase levels were measured using the Lovibond method, while data on pesticide use behavior were collected through structured interviews. Data presented in frequency and proportion distributions and tested with logistic regression to identify determinant factors.Results: A total of 27.9% of respondents experienced pesticide poisoning. Factors significantly associated with pesticide poisoning were the use of personal protective equipment (p = 0.000; OR = 13.5), spraying method (p = 0.000; OR = 13.5), and pesticide management (p = 0.000; OR = 90). In multivariable analysis, poor pesticide management remained independently associated with pesticide poisoning (OR = 33.12; p = 0.008).Conclusions: Reduced cholinesterase activity was observed in more than one-quarter of farmers. Unsafe pesticide management practices were strongly associated with pesticide poisoning. Regular health monitoring and agricultural extension are recommended. As a follow-up, the Smart Farmers for Pesticides Movement (GENTARIDA) was established to promote safe pesticide practices among farmers.